SIGNIFIKANSI PREVENTIVE EXPENDITURES VALUATION DALAM BIOPROSPEKSI SUMBERDAYA GENETIK DI INDONESIA - Wahyu Yun Santoso (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Great potential of Indonesian biodiversity provides benefits and challenges as well in its protection and preservation. One critical issue arise along the rapid development of biotechnology is on genetic resources commersialization. Precautionary approach as mandated by Convention on Biological Diversity alternatively can be used as an opportunity for performing sustainable use of genetic resources. However, the lack of economic valuation of national natural resources is became an obstacle. Preventive expenditures is a common expenditures spent to avoid or prevent externalities. This normative research aims to find the significance of this method, on the basis of precautionary approach, to valuate the genetic resources within bioprospecting applications.